Cosmopolitics as a Taste for Cunning: The Plural of the Otherwise and the Principles of Stereoscopy - Bensusan, Hilan (Das Questões, 2021)
The idea of a cosmopolitics is considered in terms of the many stories that are simultaneously told by this cosmos. Those stories interact in several political ways and often require a taste for cunning to be heard. This stereoscopic feature of cosmopolitics is considered in terms of some of its salient dimensions: it relies on the ecology of practices, on the anthropology of nature, on the history of beyng, on spectrology and on general economy. As a consequence of this analysis of the cosmopolitical action (or event), this cosmos is persistently open to the otherwise.